Effects Foetal Wastage and Some Abnormal Conditions in Slaughtered Ovine - Ramalan S. M.; Zaifada A. U.; Olatunji E. A.; Alagbe J. O. (Scholars Digest Publishing, 2022)
The study was conducted on 1,573 pregnant ewes slaughtered at Gwagwalada abattoir between September to October, 2003. The study was conducted to investigate foetal wastages associated with the slaughter of pregnant ewes and to detect some diseases or lesions associated with slaughtered sheep at the abattoir. The results obtained from the investigation revealed overall average foetal recovery rate of about 388 foetuses (24.7 %). The slaughtering of pregnant animals was significantly high in September (26.4 %) than in October (23.3 %). Pathological lesions and diseased conditions found to be associated with slaughtered sheep at the abattoir included: Abscesses 6.5 %, Cirrhosis of the liver 54.0 %, Helminthiasis 5.0 %, Mastitis 0.1 %, Pneumonia 10.8 % and Tuberculosis 0.57 %. Statistical analysis revealed significant differences (P>0.05) between the number of foetuses slaughtered. It is evident from the results of this study that the slaughter of pregnant ewes adversely effects the economics of sheep production in the areas covered by this study. It is therefore required that appropriate government legislation and policy efforts are required for effective monitoring and dissemination of information relevant to prevent unwholesome practices and prevent certain diseases which could be of enormous economic and public health significance in Nigeria.
Keywords: Diseases, Sheep, Foetal wastages, Gwagwalada abattoir.